Role of transient receptor potential ankyrin 1 channels in Alzheimer's disease. Issue 1 (December 2016) - Lee, Kuan-I; Lee, Hsueh-Te; Lin, Hui-Ching; Tsay, Huey-Jen; Tsai, Feng-Chuan; Shyue, Song-Kun; Lee, Tzong-Shyuan
Abstract Background Transient receptor potential ankyrin 1 (TRPA1) channel plays an important role in pain and inflammation. However, little is known about the significance of the TRPA1 channel in the pathophysiology of Alzheimer's disease (AD). Methods Wild-type (WT), TRPA1−/−, amyloid precursor protein (APP)/presenilin 1 (PS1) transgenic (APP/PS1 Tg) mice, the mouse model of AD, and APP/PS1 Tg/TRPA1−/− mice were used to examine the role of TRPA1 in pathogenesis of AD. Western blot was used for protein expression; immunohistochemistry was used for histological examination. The mouse behaviors were evaluated by locomotion, nesting building, Y-maze and Morris water maze tests; levels of interleukin (IL)-1β, IL-4, IL-6 and IL-10 and the activities of protein phosphatase 2B (PP2B), NF-κB and nuclear factor of activated T cells (NFAT) were measured by conventional assay kits; Fluo-8 NW calcium (Ca2+ ) assay kit was used for the measurement of intracellular Ca2+ level in primary astrocytes and HEK293 cells. Results The protein expression of TRPA1 channels was higher in brains, mainly astrocytes of the hippocampus, from APP/PS1 Tg mice than WT mice. Ablation of TRPA1-channel function in APP/PS1 Tg mice alleviated behavioral dysfunction, Aβ plaque deposition and pro-inflammatory cytokine production but increased astrogliosis in brain lesions. TRPA1 channels were activated and Ca2+ influx was elicited in both astrocytes and TRPA1-transfected HEK293 cells treated with fibrilized Aβ1–42 ; these were abrogated by pharmacological inhibition of TRPA1 channel activity, disruption of TRPA1 channel function or removal of extracellular Ca2+ . Inhibition of TRPA1 channel activity exacerbated Aβ1–42 –induced astrogliosis but inhibited Aβ1–42 –increased PP2B activation, the production of pro-inflammatory cytokines and activities of transcriptional factors NF-κB and NFAT in astrocytes and in APP/PS1 Tg mice. Pharmacological inhibition of PP2B activity diminished the fibrilized Aβ1–42 –induced production of pro-inflammatory cytokines, activation of NF-κB and NFAT and astrogliosis in astrocytes. Conclusions TRPA1 − Ca2+  − PP2B signaling may play a crucial role in regulating astrocyte-derived inflammation and pathogenesis of AD.